Pemanfaatan Kemasan Makanan sebagai Media Kontekstual dalam Pembelajaran Teks Prosedur pada Siswa Kelas IV Sekolah Dasar - Wibawa, Gandung Adhi; Iswatiningsih, Daroe (YASIN, 2025)
The teaching of procedural texts in elementary schools is often conducted in a theoretical manner and lacks connection to students’ real-life experiences, resulting in limited understanding of text structure and minimal active engagement in the learning process. This study aims to describe the use of food packaging as contextual media in teaching procedural texts to fourth-grade elementary students. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The research subjects consisted of six fourth-grade students who learned procedural texts in Bahasa Indonesia using food packaging, such as instant noodle, powdered milk, and tea bag packages as text sources. The findings reveal that using food packaging helps students understand the structure of procedural texts more concretely and enjoyably. Observations indicated increased enthusiasm and confidence as students rewrote procedural steps based on the information presented in the media. In-depth interviews confirmed that students felt more supported and engaged when learning through contextual media compared to traditional textbooks. The study concludes that food packaging, as contextual learning media, is effective in enhancing students’ comprehension and learning motivation. The implications suggest that teachers can utilize simple, familiar objects as relevant instructional tools to foster active participation and strengthen procedural literacy within everyday contexts.